2020
DOI: 10.3390/molecules25081793
|View full text |Cite
|
Sign up to set email alerts
|

CC12 Induces Apoptotic Cell Death and Cell Cycle Arrest in Human Glioblastoma Cell Lines and Mouse Xenograft Model

Abstract: Among central nervous system tumors, glioblastoma (GBM) is the most common and the most malignant type. Even under current standard treatments, the overall survival rate is still low and the recurrence rate is high. Therefore, developing novel and effective therapy is urgently needed. CC12, a synthesized small molecule, was evaluated for the potential anti-GBM effects in two GBM cell lines, U87MG and U118MG. The observations of cell morphology, MTT assay, flow cytometry-based apoptosis after CC12 treatment, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Cancer cells cultured in 2D often have little resistance to drugs [22][23][24]. For example, cancer cells are most sensitive to pro-apoptotic treatments when culture in plastic dishes may not be translatable to the clinic [25]. Importantly, 2D cancer models lack cell heterogeneity observed in clinical samples in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells cultured in 2D often have little resistance to drugs [22][23][24]. For example, cancer cells are most sensitive to pro-apoptotic treatments when culture in plastic dishes may not be translatable to the clinic [25]. Importantly, 2D cancer models lack cell heterogeneity observed in clinical samples in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cell ratio was measured by Annexin V/7AAD staining followed by flow cytometry analysis. Simultaneous staining of cells with Annexin V/7-AAD allows the discrimination of intact cells (Annexin V-/7-AAD-), early apoptotic (Annexin V+/7-AAD —), and late apoptotic or necrotic cells (Annexin V+/7-AAD +) [ 46 ]. Briefly, U373 cells (1 mL containing 10 6 per well) were seeded into 24-well microplates and incubated by 24 h. Then, 1 mL of solutions with increasing concentrations of perezone and perezone angelate diluted in fresh medium containing 2% ethanol were added to the respective wells, obtaining a final concentration of 6.25 and 50 μM ( n = 3) and incubated for an additional 48 h (final concentration of ethanol 1%), employing cells without treatment as control.…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that gypenoside LI exhibits the ability to inhibit the proliferation and migration of human breast cancer cells, induce apoptosis, and arrest the cell cycle at the G0/G1 phase by modulating E2F1 [14]. Fann and colleagues found that treatment with anthraquinone (CC12) resulted in reduced Bcl2 protein expression in two glioblastoma cell lines, 87MG and U118MG, suggesting that CC12 induces apoptosis in tumor cells and arrests cells in the G1 phase [15].…”
Section: Introductionmentioning
confidence: 99%